Systemic correction of osteoporosis of the alveolar processes of the jaw in complex treatment of patients with generalized periodontitis - K.E. Pechkovskyi; M.M. Kolotilov; I.M. Pechkovska; T.O. Timokhina (Medičnì Perspektivi, 2022)
Generalized periodontitis is accompanied by progressive bone atrophy of the alveolar process of the jaws. The first signs of osteoporosis appear in the alveolar process already in the early stages. Complex treatment of generalized periodontitis includes, first of all, an etiopathogenetic approach. The object of the study is to investigate the effectiveness of biotherapeutic correction of osteoporosis of the alveolar processes of the jaws in the complex treatment of patients with generalized periodontitis adding melatonin and vitamin D. The study involved 121 patients aged from 26-40 years with generalized periodontitis of initial-I and I stages with a chronic course, and 45 apparently healthy volunteers from the control group. All patients gave voluntary informed consent to participate in the study. Groups of patients were randomized approximately by same age and gender. Before onset of treatment and 6 months after the complex treatment the level of vitamin D and melatonin level was measured and examined for osteoporosis using a cone-beam computed tomography. In order to give a qualitative and quantitative assessment of the state of mineralization of the spongy and compact bone tissue of the alveolar processes of the jaws histographic analysis of computed tomography was used. 55 patients in addition to traditional local treatment were added vitamin D intake of 4000 IU/d with meals and melatonin intake of 1.5 mg at bedtime for 1 month. It was stated, that level of melatonin in saliva is inversely proportional to the level of vitamin D in the blood serum in patients with generalized periodontitis and patients from the group with clinically healthy periodontium. Using  melatonin and vitamin D in the complex of treatment of patients with generalized periodontitis leads to an increase X-ray density of bone tissue of the alveolar processes of the jaws, which allows to achieve restoration of bone density of alveolar processes and longer stabilization of dystrophic – inflammatory process in the periodontium. To strengthen the bone tissue of the alveolar processes of the jaws in patients with generalized periodontitis, it is advisable to use  melatonin and  vitamin D in a complex treatment.